Health Human Capital Investment and Economic Growth - Zheng, Lili; Lu, Yuan (Technium Social Sciences Journal, 2020)
Economic growth depends on factor inputs, and health human capital investment is a very important factor input. We set up a three-period overlapping generation model of personal health investment and government public health investment in the formation of physical capital and human capital and its impact on economic growth. Our findings show that health human capital investment can increase economic growth. We also conducted empirical research on the relationship between health human capital investment and economic growth by using China’s provincial panel data from 1999 to 2016. The robustness test of endogenous and interactive term regression confirms our results. We found that individual health investment has the greatest impact on economic growth. Therefore, China's health strategy is consistent with the policy of economic growth. China should further expand health investment and optimize the structure of health investment to promote its economic growth.